The stinky cheese vacation - Stilton, Geronimo (New York : Scholastic, 2014)
Heading to Penny Pincher Castle to visit his uncle for what he thinks will be a nice vacation, Geronimo is instead put to work.
Keywords: Children's stories; Action and adventure fiction